Unlocking the Power of Oom and Tannie: How Forms of Address Shape Perception and Respect in Afrikaans - Carla Ellis (Languages)
Although some research on forms of address toward adults in the South African context has been conducted in the past, there remains a gap regarding the use of oom and tannie as a specific informal Afrikaans form of address. This study comprises both a review of the existing literature and an empirical investigation to address this gap. A mixed-methods approach was used to conduct the empirical investigation. Quantitative data were collected through electronic questionnaires completed by adults and learners. Qualitative data were collected by conducting semi-structured interviews. Analysis of the data indicated that the use of oom and tannie is still prevalent in the Afrikaans-speaking community, demonstrating a high frequency of use. From the data, it becomes evident that age, respect, familiarity, social class, and status serve as determining factors in the use of oom and tannie. The age difference between speaker and addressee that serves as the accepted norm for using oom and tannie remains ten years or more. It seems that the Afrikaans community is moving toward a more informal and solidary society, with oom and tannie or first names being preferred over the use of titles. Without a doubt, oom and tannie are used in the Afrikaans community as alternative forms of respect.